Plant Population and Fungicide Treatment Reduce Winter Wheat Yield Gap in Kansas - B. R. Jaenisch; R. P. Lollato (Kansas Agricultural Experiment Station Research Reports, 2018)
Despite the large winter wheat yield gap in Kansas, limited research is available on integrated agronomic practices to increase grain yield. Our objective was to quantify the contribution of individual and combined management practices to reduce wheat yield gap. An incomplete factorial treatment structure established in a randomized complete block design was conducted in three locations in Kansas during 2016–2017 to evaluate the impacts of 14 treatments on yield and grain protein concentration of the modern wheat variety ‘Everest.’ We individually added six treatments to a low-input standard control or removed from a high-input intensive control, which received all treatments. Treatments were: additional nitrogen, sulfur or chloride, increased plant population, foliar fungicide, and plant growth regulator. In Manhattan, the intensive control increased grain yield by 6 bu/a as compared to the standard control, mostly led by additional nitrogen, sulfur, increased population, and fungicide (3–6 bu/a). In Belleville and Hutchinson, foliar fungicide increased grain yield on average by 19 bu/a. Additional nitrogen was the only treatment that increased grain protein concentration across all locations. Our results suggest that integrated pest management should be preferred over an intensive program with prophylactic pesticide application.
Keywords: wheat plant population; wheat fungicide treatment; wheat yield gap; Kansas wheat; Agronomy field research